Methamphetamines and Serious Injection-Related Infections: Opioid Use Care Continuum and Opportunities to End Alabama's Drug Crisis. (30th December 2022) - Levy, Sera; Bassler, John; Gagnon, Kelly; Prados, Myles; Jeziorski, Madison; McCleskey, Brandi; Crockett, Kaylee; Li, Li; Bradford, Davis; Cropsey, Karen; Eaton, Ellen
Abstract: Background: Increasingly, injection opioid use and opioid use disorder (OUD) are complicated by methamphetamine use, but the impact of stimulant use on the care of people who inject drugs (PWID) with serious injection-related infections (SIRIs) is unknown. The objective of this study was to explore hospital outcomes and postdischarge trends for a cohort of hospitalized PWID to identify opportunities for intervention. Methods: We queried the electronic medical record for patients hospitalized at the University of Alabama at Birmingham with injection drug use–related infections between 1/11/2016 and 4/24/2021. Patients were categorized as having OUD only (OUD), OUD plus methamphetamine use (OUD/meth), or injection of other substance(s) (other). We utilized statistical analyses to assess group differences across hospital outcomes and postdischarge trends. We determined the OUD continuum of care for those with OUD, with and without methamphetamine use. Results: A total of 370 patients met inclusion criteria—many with readmissions (98%) and high mortality (8%). The majority were White, male, and uninsured, with a median age of 38. One in 4 resided outside of a metropolitan area. There were significant differences according to substance use in terms of sociodemographics and hospital outcomes: patients with OUD/meth were more likely to leave via patient-directed discharge, but those with OUD only had the greatest mortality. Comorbid methamphetamine use did not significantly impact the OUD care continuum. Conclusions: The current drug crisis in AL will require targeted interventions to engage a young, uninsured population with SIRI in evidence-based addiction and infection services. Abstract : In response to the increasing prevalence of concurrent opioid and stimulant use among patients hospitalized for serious injection related infections, this retrospective cohort study explores hospital outcomes and post-discharge trends across a contemporary population of individuals who inject drugs.